The influence of entrepreneurial bricolage and design thinking on opportunity development - Lindie Schuld; Cornelia M. Joynt; Alex J. Antonites (The Southern African Journal of Entrepreneurship and Small Business Management, 2023)
Background: Entrepreneurial activity in an efficiency-driven economy is fundamental to economic growth, yet its sustainability and opportunities are concerning. Both entrepreneurial bricolage and design thinking could enhance opportunity development, but their effectiveness and incorporation into an integrated approach to opportunity advancement require further investigation.